ETOS KERJA 4.0: ADAPTASI APARATUR SIPIL NEGARA DALAM MENGHADAPI TANTANGAN REVOLUSI INDUSTRI - Hernansi Simamora, Ruth; N.M Sirait, Donna; Caesar Akbar, Muhammad; Lumbangaol, Erwin (Penerbit Lafadz Jaya, 2024)
This study aims to apply the model of technology acceptance or extension and adaptation, and the mixed methods approach is applied in this paper to explore the attitudes and concerns of a civil servant in facing the challenges of the industrial revolution. This type of research conducted by researchers is descriptive qualitative. Descriptive qualitative is a type of qualitative research that explores the characteristics of a phenomenon, not explaining the underlying causes or mechanisms. This involves the collection and analysis of data in the form of words, pictures, or other forms of non-numeric information regarding applying a model of technology acceptance or extension and adaptation and a mixed methods approach is applied in this paper to explore the attitudes and concerns of a civil servant in dealing with challenges of the industrial revolution. The research technique that the authors use to collect data in this study through observation or interviews. The results of this study indicate that in general the state civil apparatus should be able to distinguish between interventions that are primarily targeted at the cultural background of each individual and interventions that are primarily targeted at organizations.